The Relationship Between Helicobacter Pylori Infection And Childhood Idiopathic Thrombocytopenic Purpura - Abbas, Sawsan S.; Hadi, Tariq M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Idiopathic thrombocytopenic purpura , a disorder characterized by autoantibody mediated platelets destruction causing decreased number of circulating platelets manifest as bleeding tendency. Since the discovery of Helicobacter pylori (H. pylori ) several studies have been published concerning a hypothetical role of this bacteria in idiopathic thrombocytopenic purpura. Aim of the study: Evaluate the pathogenic correlation between H.pylori infection and idiopathic thrombocytopenic purpura. Patients and Method: A cross sectional study was done on 30 cases of idiopathic thrombocytopenic purpura admitted to the Pediatric Hemato-Oncology unit in ALKadhimiyia Teaching Hospital and 20 cases of sex and age matched healthy children as a control to determine the relation between H. pylori infection and idiopathic thrombocytopenic purpura. The peak age for idiopathic thrombocytopenic purpura was between ( 6-10 years) of age, (43.33%). Male : female ratio equal to 2:1 . ELIZA test was used to measure the serum IgG antibody titer against H. pylori , 5 cases of idiopathic thrombocytopenic purpura was found to be positive for H.pylori (16.67%)while the test was negative in all of the control group (100%) , Results: a result which is statistically highly s i g n i f i c a n t , p - value<0.05. Of the positive cases 3 (60%) was chronic idiopathic thrombocytopenic purpura and two cases (40%) was acute idiopathic thrombocytopenic purpura. Patients with positive test were older than those with negative test. The mean platelet count was less in the positive than those with negative test. A weak inverse correlation was found between platelet count and H.pylori serum antibody titer( r- value equal to - 0.13437). The test was sensitive in (20%) and specific in (100%) of cases. Conclusion: H. pylori infection may play a role in the initiation of idiopathic thrombocytopenic purpura and eradication of H.pylori infection can cure idiopathic thrombocytopenic purpura specially in chronic and resistant cases. The ELIZA test can be used as a screening test to detect H.pylori infection in children with idiopathic thrombocytopenic purpura.